2011
DOI: 10.1142/s0218216511008954
|View full text |Cite
|
Sign up to set email alerts
|

Planar and Spherical Stick Indices of Knots

Abstract: The stick index of a knot is the least number of line segments required to build the knot in space. We define two analogous 2-dimensional invariants, the planar stick index, which is the least number of line segments in the plane to build a projection, and the spherical stick index, which is the least number of great circle arcs to build a projection on the sphere. We find bounds on these quantities in terms of other knot invariants, and give planar stick and spherical stick constructions for torus knots and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There are two comments worth making here. First, Colin Adams et al [2,3] have looked at the projection stick index of a knot or link. This is the minimum number of sticks needed for a polygonal diagram of K. (For example, the projection stick number of the trefoil is 5, while the usual stick number is 6.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two comments worth making here. First, Colin Adams et al [2,3] have looked at the projection stick index of a knot or link. This is the minimum number of sticks needed for a polygonal diagram of K. (For example, the projection stick number of the trefoil is 5, while the usual stick number is 6.)…”
Section: Discussionmentioning
confidence: 99%
“…The first author [11] then used results of [17] to prove that any knot or link type K contains a folded ribbon knot K w such that (3) Rib(K w ) ≤ 72Cr(K) 3/2 + 32Cr(K) + 12 Cr(K) + 4.…”
Section: Introductionmentioning
confidence: 99%
“…We can define the projection stick index to be the minimum number of sticks needed for a polygonal knot diagram of K. We have just seen the unknot has projection stick index two, and regular stick index three. Together with undergraduate students, C. Adams [2,3] showed that the projection stick index of the trefoil knot is five, while the regular stick index is six (illustrated in Figure 2). Indeed, we expect the projection stick index to be smaller than the stick index since the edges in the knot diagram are not rigid sticks in space, they have crossing information instead.…”
Section: Modeling Folded Ribbon Knotsmentioning
confidence: 99%
“…The projection stick number is the least number of line segments in any projection of a polygonal embedding of a knot. Together with undergraduate students, Colin Adams has given some results about the projection stick index of knots in [2,3]. For example, the projection stick index of the trefoil knot is five.…”
Section: Projection Stick Index and Ribbonlengthmentioning
confidence: 99%